PEDAGOGIC WORK SYSTEM IN A MODERN UNIVERSITY - Emma G. Kul’Chieva; Aslan E. Batyrov (Высшее образование в России)
Pedagogic work is an integral part of the education process. In the article the authors give an overview of the modern system of pedagogic work based on the North-Ossetian State University experience.The authors explain the way the work is organized in compliance with federal law and the University concept idea. Along with that the University supports informal ways of students’involvement, since pedagogic system is considered first as an interaction between faculty andstudents both in academic and out-of-class spheres. As the authors suggest, in this case theUniversity is not only the center for professional education, but also the ground for cultural development and social modernization.